2022
DOI: 10.1097/aud.0000000000001281
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers as Patient-Site Facilitators in Adult Hearing Aid Services via Synchronous Teleaudiology: Feasibility Results from the Conexiones Randomized Controlled Trial

Abstract: Objectives: The purpose of this study was to investigate the feasibility of Community Health Workers (CHWs) as patient-site facilitators in teleaudiology-facilitated hearing aid services to improve hearing aid rehabilitation outcomes for older Hispanic/Latino adults in a medically underserved, rural, US-Mexico border community. Design: A total of 28 adults (aged 55 to 89) with bilateral hearing loss participated in this study. Individuals were randomized to one of two teleaudiology intervention arms that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…While the use of implementation research and/or outcome frameworks for translating evidence-based practice to clinical service delivery is gaining momentum, it is still underused in tele-audiology service implementations. Only one recent study reported the use of implementation science framework to investigate the feasibility outcomes of a 17-week tele-audiology hearing aid service 65. Similar efforts for long-term implementation will offer deeper insights on sustainability aspects.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of implementation research and/or outcome frameworks for translating evidence-based practice to clinical service delivery is gaining momentum, it is still underused in tele-audiology service implementations. Only one recent study reported the use of implementation science framework to investigate the feasibility outcomes of a 17-week tele-audiology hearing aid service 65. Similar efforts for long-term implementation will offer deeper insights on sustainability aspects.…”
Section: Discussionmentioning
confidence: 99%
“…CBPR is compatible with a variety of research methodologies: randomized control trials, mixed methods studies, surveys, qualitative studies, and quasi-experimental studies (Viswanathan et al 2004). The CBPR approach has been successfully employed in these hearing healthcare research studies: the Oyendo Bien clinical trial (Marrone et al 2017), the Conexiones clinical trial (Coco et al 2023), and the Hearing Norton Sound clinical trial (Emmett et al 2019).…”
Section: Changing the Paradigm Of Hearing Researchmentioning
confidence: 99%
“…This mHealth program has demonstrated the potential for low-cost, scalable impact, with positive reports on applicability and accessibility from all community members 16 . The use of CHWs facilitating teleaudiology has also been shown to be a feasible strategy for adults 17 . Service-delivery models that utilize CHW allow scarce resources like trained professionals such as audiologists to support these programs through training, remote monitoring, and surveillance.…”
Section: Innovative Community-based Hearing Aid Provisionmentioning
confidence: 99%